A case of alcohol-related prolonged withdrawal and delirium tremans - Balcı Şengül, Ceyhan; Şengül, Cem (Journal of Dependence, 2014)
Alcohol withdrawal syndrome is a set of symptoms that can occur when an individual reduces or stops alcohol consumption after long periods of alcohol use. Symptoms may differ from benign tremor to transient hallucinations (auditory, visual or tactile), disorientation, confusion and delirium tremens. Withdrawal usually begins one to three days after the last drink and can last for up to one week. In this paper, we presented a case of prolonged alcohol withdrawal and delirium tremens. 42 year old male patient with a history of 25 years of alcohol use was hospitalized for delirium tremens 5 weeks after cessation of alcohol.